Climate Change and Media Representation: A Multimodal Discourse Analysis of Clean Green Pakistan Policy from Eco-linguistic perspective - Dr. Muhammad Haseeb Nasir; Dr. Azhar Habib; Dr. Muhammad Yousaf (University of Chitral Journal of Linguistics and Literature, 2022)
The study aims to explore the constructive/destructive role of print media advertisements in disseminating ecological discourse. There has been a great threat to climate and it has become imperative to understand the philosophy behind (re)production of text where language plays central role advocating such ecological narratives that protect/destroy our environment at large. Media, due to vast readership/viewership, (re)frames the ideology of people and paves the way for environmental balance/imbalance without much effort.  This study also highlights as to how linguistic features such as: salience, metaphor and framing are materialized to make the discourses appear natural and persuasive. The data is comprised of 5 print media advertisements being published in popular English newspapers. The sampling technique is purposive and selection of the advertisement timeframe is from 2019 to 2021. The conceptual underpinning of the study is Stibbe’s (2015) and Kress & Leeuwan (2006) model which helps the readers critically analyze the text. The study finds that these advertisements present layers of meanings metaphorically and highlight the importance of ecologically constructive discourse to bring about climate/environment sustainability.